Is the total sulfur amino acid:lysine ratio for lactating sows greater than 50%? - Schneider, J.D.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 75 lactating sows were used in a study to determine whether the ratio of total sulfur amino acid (TSAA) to lysine calculated from the NRC (1998) is adequate for lactating sows. Low and high sulfur amino acid diets were formulated to contain a (true ileal digestible (TID) TSAA content of 0.44 or 0.57%, respectively. Both experimental diets were based on corn and soybean meal and were formulated to contain 0.88% TID lysine (0.97% total lysine). Thus, the TID TSAA:lysine ratios were 50 and 65% for the two experimental diets, respectively. Both experimental diets contained 0.37% L-lysine HCl, with other amino acids (isoleucine, threonine, tryptophan, and valine) added to ensure that TSAA were the first limiting amino acids. Sows were farrowed in three farrowing groups and were randomly allotted to the dietary treatments on the basis of parity. The lactating sows fed the 0.57% T had greater ADFI than did sows fed the 0.44% TSAA diet (P<0.05). Sow weight loss was not affected by lactation treatment, but sows fed the diet with more TSAA had greater (P<0.02) litter weight gain, heavier (P<0.01) litter weaning weights, and heavier (P<0.06) individual pig weaning weight than did sows fed the 0.44% TSAA diet. These data indicate that the basal diet can be used in future experiments to titrate the TSAA requirement of the sow. Results also indicate that the TID TSAA requirement is greater than 0.44% and the TSAA:lysine ratio is greater than 50% for lactating sows. Because amino acid recommendations from the NRC (1998) suggest that the TID TSAA:lysine ratio is approximately 48%, more research is warranted to more adequately determine the TID TSAA:lysine ratio for lactating sows.
Swine research, 2005 is known as Swine day, 2005
Keywords: TSAA; Lysine; Lactating sow; Swine